The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1111/ajr.12140
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine in the Northern Territory: An assessment of patient perceptions in the preoperative anaesthetic clinic

Abstract: Our study confirms the acceptability of telemedicine in the remote assessment of preoperative patients in the Northern Territory, with positive perceptions in all four domains.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
60
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(67 citation statements)
references
References 11 publications
3
60
0
Order By: Relevance
“…10,22,23,28 Two studies explored the Indigenous patient's perspective on the use of telehealth. One study reported a 75% preference for teleconsultations over face-to-face consultations, 34 whereas Mooi et al 25 reported that 100% of Indigenous patients preferred telehealth. The higher preference in the latter study may be explained by service type.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…10,22,23,28 Two studies explored the Indigenous patient's perspective on the use of telehealth. One study reported a 75% preference for teleconsultations over face-to-face consultations, 34 whereas Mooi et al 25 reported that 100% of Indigenous patients preferred telehealth. The higher preference in the latter study may be explained by service type.…”
Section: Discussionmentioning
confidence: 99%
“…Store-and-forward services were used in screening programs for ear health, [22][23][24]28 and diabetic eye disease. 29,30 Video conferencing was used to: provide medical consultations, 25,26,[31][32][33][34][35] for the supervision of chemotherapy administration, 25,26,35 and for the delivery of speech rehabilitation therapy. 36 Remote telehealth monitoring was used for in-home/ in-hub monitoring of chronic diseases in the Staying Strong pilot project.…”
Section: Telehealth Service Characteristics and Patient Interactionsmentioning
confidence: 99%
“…1 The positive patient responses have certainly inspired me to continue to advocate for this technology. 1 The positive patient responses have certainly inspired me to continue to advocate for this technology.…”
mentioning
confidence: 99%
“…1 The community rehabilitation team I lead is participating in a regional stroke telerehabilitation project, utilising a hub and spoke model. 1 Additionally, these patients may already be unwell and have considerable distances to traverse. Patients have not only been willing to participate enthusiastically but they also report better care coordination and communication, reflecting this study's outcomes.…”
mentioning
confidence: 99%
See 1 more Smart Citation